Characteristics associated with diagnostic yield of imaging for deep venous thrombosis and pulmonary embolism in the emergency department, hospital, and office settings: An Optum Clinformatics claims database study (2015–2019). Issue 224 (April 2023) - Rohatgi, Nidhi; Dahlen, Alex; Berube, Caroline; Weng, Yingjie; Wintermark, Max; Ahuja, Neera
Abstract: Background: Different patient characteristics influence the decision to order diagnostic imaging for deep venous thrombosis (DVT) and pulmonary embolism (PE) in different settings (emergency department (ED), hospital, and office). Diagnostic yield is defined as the proportion of tests that report positive results. We hypothesize different patient characteristics are associated with higher or lower diagnostic yield of imaging for DVT and PE in different settings. Methods: We used Optum Clinformatics™ national claims database (2015–2019) to assess the diagnostic yield of imaging for DVT and PE in three settings: (a) ED discharge, (b) Hospitalized, and (c) Office. We studied the patient characteristics associated with diagnostic yield using logistic regression. Results: Diagnostic imaging for DVT and PE was performed in 1, 502, 417 and 710, 263 visits, respectively. Diagnostic yield for DVT and PE was 9.8 ± 0.1 % and 12.7 ± 0.1 %, respectively in the overall cohort. In the ED discharge, hospitalized, and office settings, diagnostic yield for DVT was 10.4 ± 0.1 %, 16.9 ± 0.1 %, and 6.5 ± 0.1 %, respectively, and that for PE 6.4 ± 0.1 %, 18.7 ± 0.1 %, and 8.8 ± 0.2 %, respectively. Of the patients who underwent imaging for DVT, higher diagnostic yield was more likely with thrombophilia, central venous access, and cancer. Of the patients who underwent imaging for PE, higher diagnostic yield was most likely with thrombophilia, respiratory failure, and heart failure or acute myocardial infarction. Conclusions: In each setting, different patient characteristics influence the diagnostic yield of imaging for DVT and PE and can inform clinical practice. Judicious use of imaging for DVT and PE could reduce costs and avoid exposure to radiation and contrast.